FGD Penggunaan Analisis SWOT untuk Menganalisis Karakteristik Raudhatul Athfal dalam Kurikulum Merdeka bagi Aktivis Pejuang Raudhatul Athfal (RA) Indonesia - Novan, Novan Ardy Wiyani; Ria Yuniawati; Siti Sutanti (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This community service activity was motivated by the inability of RA teachers to analyze the characteristics of RA in implementing the independent curriculum. The aim is to provide learning services to RA teachers in Indonesia in using SWOT analysis techniques to analyze RA characteristics in an independent curriculum for Indonesian RA activists through FGD activities. Participants in the FGD activity were 36 people. The implementation consists of 5 stages, namely investigation, preparation, implementation, reflection and demonstration. At this investigation stage the author investigates the problem that will be solved through FGD. In the preparation stage the author plans the implementation of FGD activities. At the implementation stage, FGD activities were carried out. At the reflection stage, feedback is provided on the results of the FGD at the implementation stage. At the demonstration stage, it was demonstrated how to describe the characteristics of RA based on the results of a SWOT analysis using a deductive mindset. It can be concluded that the results of the SWOT analysis can be used as material for compiling an analysis of RA characteristics because it describes the various potentials possessed by RA. Then the impact of carrying out this service activity is that the FGD participants have the ability to analyze the characteristics of RA in implementing the independent curriculum using the SWOT analysis technique.